Simplified Classification of Focal Cortical Dysplasia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
Sections of cortex from 52 of 224 (23%) patients with cortical dysplasia, operated on for drug-resistant partial epilepsy, were retrospectively re-examined histologically at Niguarda Hospital, and Istituto Nazionale Neurologico 'C. Besta', Milan, Italy.